A Flexible Asymmetric NaFePO4/Carbon Cloth Supercapacitor Using Crosslinked Polyacrylate Gel as Electrolyte. Issue 39 (18th October 2021) - Quan, Yufei; Wang, Sumin; Liu, Pan; Shen, Zhiruo; Wang, Qiguan
Abstract: With the development of light‐weight and bendable electric devices, nowdays, solid‐state supercapacitive devices have attracted great attention, in which the classic polymeric electrolytes such as polyvinyl alcohol and polyethylene oxide copolymers are generally used. However, the microphase separation in these polymers and low conductivity affect the ions transfer and the energy‐storage performance. In this work, a crosslinked sodium polyacrylate gel (NaPA) is synthesized to replace conventional polymeric electrolyte. Because NaPA is a kind of polymeric salt which has high native degree of ionization in water, the NaPA gel shows low resistance to ion transportation. By using NaPA gel as the electrolyte and carbon cloth as current collector, a flexible solid asymmetric supercapacitor assembled by positive NaFePO4 /carbon cloth and negative activated carbon/carbon cloth electrode shows the maximum capacitance of 46.33 mF cm −2 at 1 mA cm −2, with a high stability of 87.33 % retention during 5000 charge and discharge cycles. Moreover, this flexible asymmetric supercapacitors showed nearly unchanged capacitance under different bending angles. It is found that the Na + diffusion coefficient in NaFePO4 /CC//NaPA supercapacitor is 8.05×10 −14  cm 2  ⋅ s, remarkable higher than CC//NaPA and NaFePO4 /CC//PVA. The high diffusion coefficient and low resistance of NaPA lead to excellent capacitave performance of NaFePO4 /CC//NaPA, delivering a good application prospect. Abstract : A crosslinked sodium polyacrylate (NaPA) gel is synthesized to replace conventional polymeric electrolyte. By using NaPA gel as the electrolyte and carbon cloth as current collector, a flexible solid asymmetric supercapacitor assembled by positive NaFePO4 /carbon cloth and negative activated carbon/carbon cloth electrode shows the maximum capacitance of 46.33 mF cm −2 at 1 mA cm −2, with high flexibility and good application prospect in wearable devices.